Mali, the G5 and security sector assistance: Political obstacles to effective cooperation - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2017)
While the security situation in Mali and its border areas continues to deteriorate, the new "Force Conjointe" (FC) of the G5 Sahel states completed its first military operation in mid-November. Its aim is to make a regional contribution to the fight against terrorism and organized crime. A summit was held in Paris on 13 December to mobilise further financial and equipment support for FC. Germany and the EU are strongly committed to this project alongside France. However, efforts to enhance regional armed forces are fraught with problems. International partners prefer a capacity-building approach geared to short-term success over security sector reform and lack a coordinated strategy. The Malian government, on the other hand, preserves the status quo and is not prepared to accept its political responsibility.
Keywords: 320